2015
DOI: 10.1021/np501062f
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Constituents of the Roots of Ethiopian Podocarpus falcatus and Structure Revision of 2α-Hydroxynagilactone F and Nagilactone I

Abstract: Bioassay-guided fractionation using the human colorectal adenocarcinoma (HT-29) cell line of the methanol extract of dried roots of Podocarpus falcatus led to the isolation of two new type C nagilactones, 16-hydroxynagilactone F (1) and 2β,16-dihydroxynagilactone F (2), and the new totarane-type bisditerpenoid 7β-hydroxymacrophyllic acid (4), along with the seven known compounds 2β-hydroxynagilactone F (3), macrophyllic acid (5), nagilactone D (6), 15-hydroxynagilactone D (7), nagilactone I (8), inumakiol D (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Among the different types of triterpenoids, pentacyclic triterpnoids display the most potent anti-inflammatory and anticancer activity [ 62 ]. Addo et al [ 63 ] reported the isolation of two new nagilactones along with seven known from the root of Podocarpus falcatus (Thunb.) collected from Berga forest, Addis Alem, central Ethiopia.…”
Section: Phytochemistry Of Ethiopian Anticancer Plantsmentioning
confidence: 99%
“…Among the different types of triterpenoids, pentacyclic triterpnoids display the most potent anti-inflammatory and anticancer activity [ 62 ]. Addo et al [ 63 ] reported the isolation of two new nagilactones along with seven known from the root of Podocarpus falcatus (Thunb.) collected from Berga forest, Addis Alem, central Ethiopia.…”
Section: Phytochemistry Of Ethiopian Anticancer Plantsmentioning
confidence: 99%
“…Therefore, the structure of 2 was defined as 3b-hydroxymakilactone A ( Figure 1). Compounds 4 -12 ( Figure 1) were identified as inumakilactone B (4), [9] 2b-hydroxynagilactone F (5), [15] nagilactone F (6), [13] 2,3-dehydronagilactone F (7), [16] nagilactone G (8), [9] inumakilactone A (9), [17] makilactone M (10), [18] nagilactone C (11), [18] and l-deoxy-2-hydroxynagilactone A (12) [12] by comparing their observed NMR data with reported data. The 1D-NMR spectroscopic data of 3 (Tables 1 and 2) were coincident with reported data of 2,3-dihydro-2αhydroxypodolide, which has been identified from Ileostylus micranthus, [14] indicating that they were the same compound.…”
Section: Structural Elucidationmentioning
confidence: 99%
“…Furthermore, the X-ray diffraction experiment (flack parameter = 0.06 (3) Thus, the structure of 3 should be revised as 2,3-dihydro-2b-hydroxypodolid ( Figure 1). Compounds 4 -12 ( Figure 1) were identified as inumakilactone B (4), [9] 2b-hydroxynagilactone F (5), [15] nagilactone F (6), [13] 2,3-dehydronagilactone F (7), [16] nagilactone G (8), [9] inumakilactone A (9), [17] makilactone M (10), [18] nagilactone C (11), [18] and l-deoxy-2-hydroxynagilactone A (12) [12] by comparing their observed NMR data with reported data.…”
Section: Structural Elucidationmentioning
confidence: 99%
“…A subsequent literature search for this chemical structure revealed that the collected 1 H and 13 C NMR data for 1 matched with those of 3-deoxy-2 α -hydroxynagilactone E ( 8 ), previously isolated from Podocarpus nagi [20]. However, careful inspection of the 1 H NMR data measured in methanol- d 4 revealed that the splitting pattern and coupling constants ( J) values of H-2 (dddd, J  = 13.5, 8.5, 7.4, 4.9 Hz) shared a close similarity with those of the revised C-type podolactone 2 β -hydroxynagilactone F (H-2, dddd, J  = 12.9, 9.1, 7.2, 5.1 Hz) [21], and suggested a comparable 2 β configuration of the hydroxy group substitution at C-2. A very recent study on P. nagi reporting the X-ray structure of 3-deoxy-2 β -hydroxynagilactone E confirmed this assertion [11].…”
Section: Resultsmentioning
confidence: 99%